RUSSIAN-UKRAINIAN WAR IN THE LIGHT OF POSTCOLONIALISM - Sami Ullah Malik (Policy Research Journal, 2025)
Modern Russian-Ukrainian war is post-colonial in nature and caused by the imperial aspirations of today's Russia. The current situation of Ukraine and Russia can be considered complex configurations of dependence. Russia is primarily concerned with reintegrating the former imperial legacy into the Soviet state-political structure. Study shows, how the Western interpretation of Ukraine's history is unique in the context of post-colonial studies. Dialectical analysis is carried out on the Russian justification of modern warfare considering the Soviet and imperial legacies. Russia's war against Ukraine aims to change the post-Soviet space's dependent position and modify the global order following the demise of the USSR, it is noteworthy that this war has an anti-globalist tendency. It is emphasized that for Ukrainians the war is existential, since modern Russia de facto does not recognize either Ukraine as a state or Ukrainian identity.